Determinants of Operational Performance in Halal Culinary Businesses - Irlanita Ayuning Tyas; Siti Nur Azizah; Jalila Youmni (Journal of Digital Marketing and Halal Industry, 2025)
The growth of the halal industry at the local level shows significant dynamics; however, studies examining the determinants of operational performance in halal culinary businesses based on local wisdom remain limited. This research offers an integration of five variables social capital, halal certification ownership, innovation capability, digital transformation, and business location into a single theoretical model grounded in the Resource-Based View (RBV) to explain the operational performance of halal culinary enterprises in Ponorogo Regency. The study aims to analyze the influence of each variable on operational performance. The method employed is a mixed-methods approach with an explanatory sequential design, beginning with a qualitative phase involving in depth interviews with five business owners, analyzed using NVivo 14. The subsequent quantitative phase was conducted using SEM-PLS on 105 respondents. The findings indicate that halal certification ownership, innovation capability, and business location have a positive and significant effect on operational performance. Meanwhile, social capital and digital transformation show positive but insignificant effects. These results emphasize that halal legitimacy, innovative capability, and locational accessibility function as strategic resources capable of enhancing efficiency and operational competitiveness. In contrast, social capital and digitalization have not provided optimal contributions due to their unstructured utilization. The implications of the study highlight the need to strengthen innovation, accelerate halal certification processes, and provide policy support and digital infrastructure to improve the competitiveness of halal culinary businesses at the regional level.